The effect of the carbon emission trading scheme on a firm’s total factor productivity: An analysis of corporate green innovation and resource allocation efficiency - Wang, Bo; Yang, Maojia; Zhang, Xiang (Frontiers in Environmental Science, 2022)
This paper investigates the effect of carbon emission trading scheme on firm’s total factor productivity in China. With a sample from 2008 to 2019, applying time-varying DID method, our empirical results reveal that the carbon emission trading scheme significantly improves firm’s total factor productivity, which provides evidence on Porter’s hypothesis. Moreover, there are two channels through which the total factor productivity is impacted: corporate green innovation channel and resource allocation efficiency channel. Furthermore, the impact of carbon emission trading scheme is more pronounced for private firms, and firms in the provinces with higher institutional development, lower environmental quality, and greater law enforcement of environmental protection tend to have larger total factor productivity. Our models survive from numerous robustness checks.